Differential growth and transpiration responses among banana (Musa Spp.) hybrids—hope for breeding drought tolerant bananas? - Nansamba, Moureen; Sibiya, Julia; Gambart, Clara; Karamura, Deborah; Karamura, Eldad; Tumuhimbise, Robooni; Carpentier, Sebastien C. (Wiley, 2025)
Summary Statement This study, one of the first in its kind, uses a promising approach to phenotype and evaluate offspring and presents the evaluation of 16 East African Highland type banana hybrids ( Musa spp.) purposely bred for drought avoidance and tolerance. Despite primarily using the Musa acuminata genetic background, promising genotypes were identified.